Laser Generated In situ Fenestrations in Dacron Stent Grafts. Issue 4 (April 2016) - Sonesson, B.; Dias, N.; Resch, T.; Kristmundsson, T.; Holst, J.
Abstract : Objective/background: To evaluate if the creation of laser generated in situ fenestrations in polyester/Dacron stent grafts causes embolization. Methods: In seven pigs, Dacron stent grafts were implanted from the infrarenal aorta to the right iliac artery. Prior to placing the stent graft, a carotid artery protection filter, with a pore size of 70–200 μm, was placed in the proximal left common iliac artery. An excimer laser catheter was then advanced antegradely through the stent graft and positioned at the level of origin of the left iliac artery. A fenestration was then created with the laser probe. The carotid filter was retrieved and inspected macroscopically with magnifying glasses, for emboli and clot. Results: Seven pigs with a median weight of 90 kg (range 78–98 kg) were tested. The median operating time was 170 minutes. All laser fenestrations were successfully completed. No emboli or clot could be detected in the protection filters. Conclusion: Creation of laser generated, in situ fenestrations do not produce macroscopically visible emboli/clot. This might indicate safe usage of laser created fenestrations for endovascular arch repair and left subclavian artery revascularization.